Surviving a Genome Collision: Genomic Signatures of Allopolyploidization in the Recent Crop Species Brassica napus. Issue 3 (1st November 2017) - Samans, Birgit; Chalhoub, Boulos; Snowdon, Rod J.
Abstract : Polyploidization has played a major role in crop plant evolution, leading to advantageous traits that have been selected by humans. Here, we describe restructuring patterns in the genome of Brassica napus L., a recent allopolyploid species. Widespread segmental deletions, duplications, and homeologous chromosome exchanges were identified in diverse genome sequences from 32 natural and 20 synthetic accessions, indicating that homeologous exchanges are a major driver of postpolyploidization genome diversification. Breakpoints of genomic rearrangements are rich in microsatellite sequences that are known to interact with the meiotic recombination machinery. In both synthetic and natural B. napus, a subgenome bias was observed toward exchanges replacing larger chromosome segments from the C‐subgenome by their smaller, homeologous A‐subgenome segments, driving postpolyploidization genome size reduction. Selection in natural B. napus favored segmental deletions involving genes associated with immunity, reproduction, and adaptation. Deletions affecting mismatch repair system genes, which are assumed to control homeologous recombination, were also found to be under selection. Structural exchanges between homeologous subgenomes appear to be a major source of novel genetic diversity in de novo allopolyploids. Documenting the consequences of genomic collision by genomic resequencing gives insights into the adaptive processes accompanying allopolyploidization.